Entrepreneurship as a multidisciplinary phenomenon: culture and individual perceptions in business creation - Martínez-Martínez, Sofía Louise (Emerald, 2022)
Purpose: Entrepreneurship is presented as a vehicle for innovation and social development. Given the importance of entrepreneurship, the objective of this study was to analyze the psychological and sociological dimensions by determining the factors that explain individual perceptions and cultural support for entrepreneurship. Design/methodology/approach: Using Global Entrepreneurship Monitor (GEM) data obtained from the Adult Population Survey (APS) (N = 2,500) in the region of Andalusia (Spain), a quantitative analysis was carried out, specifically a multivariate analysis based on four-stage linear regressions. Findings: The variables examined do not explain the psychological and sociological dimensions to the same extent. The results highlight the existence of cultural homogeneity between provinces, the importance of sociodemographic variables and the influence of the entrepreneurial expectations and experiences of the population, especially in shaping individual perceptions towards entrepreneurship. Research limitations/implications: The replication of the study at the national and international levels is proposed in order to delve deeper into the cultural differences that condition entrepreneurship. Including new variables associated with entrepreneurial human capital could also be of interest. Practical implications: The results can help to improve the design and implementation of policies and programs aimed at fostering entrepreneurship through the promotion of favorable individual perceptions and entrepreneurial culture. Originality/value: The originality of this study is the consideration of individual perceptions and cultural support for entrepreneurship as dependent variables, since they are normally incorporated as explanatory factors. The results contribute to the advancement of knowledge of the entrepreneurial phenomenon through two approaches, psychological and sociological.
Keywords: Emprendimiento; Desarrollo económico y social; Entrepreneurship; Business; Cultural support for entrepreneurship; Individual perceptions; GEM; Spain